Effect of Hydroponic Maize Fodder Supplementation on Growth Performance, Nutritive Ratio and Intake of Digestible Nutrient in Gir Calves - Jediya, Hemant K.; Shende, Kavita A.; Dhuria, Rajesh K.; Vaishnava, Chandrashekar S.; Barolia, Yogesh K. (International Journal of Bio-resource and Stress Management, 2021)
A study was undertaken to assess the effect of addition of hydroponic maize fodder in concentrate mixture on growth performance of gir calves. A feeding trial of 120 days was undertaken on 16 gir calves divided in four groups of four calves. The animals in control group were fed 1.5 kg concentrate mixture, 2.5 kg groundnut straw and wheat straw ad lib. In group second, 75% of CP was met through concentrate mixture and rest through hydroponic maize fodder along with 2.5 kg groundnut straw and ad lib. wheat straw was given. While, in third group, 50% of CP was met through concentrate mixture and rest through hydroponic maize fodder and 2.5 kg of groundnut straw was given along with ad lib. wheat straw. In group fourth, 25% of CP was met through concentrate mixture and remaining by hydroponic maize fodder and 2.5 kg groundnut straw with ad lib. wheat straw was offered. Significantly higher daily weight gain, digestible crude protein percent, total digestible nutrient percent and intake of digestible dry matter and organic matter in respect of g D-1 was observed in the group in which up to 75% of crude protein of concentrate mixture was replaced by hydroponic maize fodder. Highest (p<0.01) digestible crude protein intake and total digestible nutrient intake g D-1, Kg 100 kg BW-1 and g 100 kg-1 MBS (Metabolic body size) was observed in group provided with 75% crude protein through hydroponic fodder. Hydroponics maize fodder has beneficial effect on growth performance and intake of digestible nutrients in gir calves and it can replace up to 75% of crude protein of concentrate mixture.